The influence of haemodialysis on haemodynamic measurements using transpulmonary thermodilution in patients with septic shock: an observational study - Pathil-Warth, Anita; Stremmel, Wolfgang; Schwenger, Vedat; Eisenbach, Christoph (European journal of anaesthesiology, 2013)
Context: Patients with sepsis frequently present with acute renal failure requiring intermittent renal replacement therapy and haemodynamic monitoring. To date, the effect of haemodialysis on PiCCO monitoring has not been determined. - Objective: To determine the effect of haemodialysis on the measurement of haemodynamic variables using transpulmonary thermodilution. - Design: Prospective observational study. - Setting: Medical ICU in a university hospital. - Patients: Thirty patients with sepsis and acute renal failure undergoing intermittent haemodialysis. - Interventions: None. - Main outcome measures: Cardiac index, global end-diastolic volume index and extravascular lung water index measured with or without haemodialysis. - Results: Significant correlations were found for all variables measured with and without haemodialysis (r = 0.55 to 0.91, P < 0.01). Measurements of cardiac index without and with haemodialysis were significantly different [4.71 vs. 4.18 l min−1 m−2, difference −0.54 (SD 0.70), 95% confidence interval (CI) −0.80 to −0.28; P < 0.01], as were values of global end-diastolic volume index without and with haemodialysis [864.8 vs. 775.3 ml m−2, difference −89.5 (SD 191.8), 95% CI −161.2 to −17.9; P = 0.02]. Measurements of extravascular lung water index without and with haemodialysis did not differ significantly [10.3 vs. 10.0 ml kg−1, difference −0.3 (SD 2.0), 95% CI −1.1 to 0.5; P = 0.42]. - Conclusion: Although significant correlations were found for cardiac index, global end-diastolic volume index and extravascular lung water index with and without haemodialysis, cardiac index and global end-diastolic volume index were significantly reduced during haemodialysis, but not extravascular lung water index, when measured by the PiCCO system in patients with septic shock. Although differences were small, the variability of within-patient differences may be clinically important and care should be taken in relying solely on such measurements.
Published online 29 August 2012
Gesehen am 20.12.2021